2015
DOI: 10.1074/jbc.m115.667063
|View full text |Cite
|
Sign up to set email alerts
|

Rotenone-induced Impairment of Mitochondrial Electron Transport Chain Confers a Selective Priming Signal for NLRP3 Inflammasome Activation

Abstract: Background: Mitochondrial dysfunction is considered crucial for triggering NLRP3 inflammasome activation. Results: Rotenone-induced impairment of mitochondrial electron transport chain promotes NLRP3 inflammasome activation exclusively with ATP but not with other NLRP3-activating stimulators. Conclusion: High-grade mROS and hyperpolarization are essential for NLRP3 inflammasome activation upon rotenoneinduced mitochondrial dysfunction. Significance: Mitochondrial impairment may selectively prime NLRP3 inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 35 publications
4
85
0
1
Order By: Relevance
“…Accordingly, in the present study ROT-induced mitochondrial electron transport chain (ETC) complex I inhibition and subsequent generation of ROS might have contributed to the excessive ROS generation in the presence of LPS. Consistent with our data, in a recent study ROT was found to induce NLRP3 inflammasome activation in the presence of an inflammasome activator (ATP) via a mechanism involving the generation of high grade mitochondrial ROS (Won et al, 2015). In another study, the saturated fatty acid palmitate was found to induce NLRP3 inflammasome activation and the release of IL-1β via a mitochondrial ROS-mediated mechanism (Wen et al, 2011a).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, in the present study ROT-induced mitochondrial electron transport chain (ETC) complex I inhibition and subsequent generation of ROS might have contributed to the excessive ROS generation in the presence of LPS. Consistent with our data, in a recent study ROT was found to induce NLRP3 inflammasome activation in the presence of an inflammasome activator (ATP) via a mechanism involving the generation of high grade mitochondrial ROS (Won et al, 2015). In another study, the saturated fatty acid palmitate was found to induce NLRP3 inflammasome activation and the release of IL-1β via a mitochondrial ROS-mediated mechanism (Wen et al, 2011a).…”
Section: Discussionsupporting
confidence: 92%
“…Treatment of murine macrophages with ROT leads to NLRP3 activation and IL-1β release in a delayed fashion although only in the presence of an inflammasome activator ATP (Won et al, 2015). Mitochondria targeted toxins have been shown to influence cell viability (Ferger et al, 2010), in order to rule out toxic effects of ROT on our experimental end points first we determined the effects of ROT and LPS on cell viability using the MTS assay, which measures mitochondrial dehydrogenase activity.…”
Section: Resultsmentioning
confidence: 99%
“…5d, upper panel). To provide more evidence that 25-HC could impair the function of mitochondria, we determined another indication of mitochondrial damage by co-staining with MitoTracker Green and MitoTracker Deep Red to measure the dissipation of mitochondrial membrane potential333435. Consistent with mtROS production, treatment with 25-HC caused an obvious increase in the damaged mitochondria-containing cell population (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, mitochondria do play a role during the formation of inflammasome. NOD-like receptor containing pyrin domain 3 (NLRP3) inflammasome assembly requires mitochondrial ROS generation [175] and is associated with concurrent mitochondrial depolarization and mtDNA release [176]. It has also been suggested that autophagy/mitophagy inhibition could promote NLRP3 inflammasome activation by inducing mitochondrial dysfunction, which, in turn, increases again ROS production [175] and promoting cardiolipin accumulation on OMM, another signal triggering NLRP3 inflammasome assembly [177].…”
Section: Inflammationmentioning
confidence: 99%